Constraints on English middle structures: A Lexical-Constructional analysis - Cortés-Rodríguez, Francisco J.; Mairal Usón, Ricardo (Onomázein, 2013)
This paper provides an analysis of English middle structures within the framework of the Lexical Constructional Model (LCM), which proposes a central module, the level 1 or argument module, consisting of elements of syntactically relevant semantic interpretation based on the interaction between lexical and constructional templates. Hence, the first task will be to explain the constructional template corresponding to middle sentences in English by means of the metalanguage proposed in the model. Nevertheless, and following some of the more recent—and still programmatic—proposals (cf. Cortés and Sosa, 2008; Mairal and Ruiz de Mendoza, 2008; Cortés, 2009), the Middle Template will also include its corresponding qualia features, following Pustejovsky’s (1995) semantic theory. This extended system of representation will allow us to give a principled account of the semantic (in)compatibility between lexical elements (predicates and arguments) and the middle construction.